Measuring phonetic convergence in speech production - Pardo, Jennifer (Frontiers in Psychology, 2013)
Phonetic convergence is defined as an increase in the similarity of acoustic-phonetic form between talkers. Previous research has demonstrated phonetic convergence both when a talker listens passively to speech and while talkers engage in social interaction. Much of this research has focused on a diverse array of acoustic-phonetic attributes, with fewer studies incorporating perceptual measures of phonetic convergence. The current paper reviews research on phonetic convergence in both non-interactive and conversational settings, and attempts to consolidate the diverse array of findings by proposing a paradigm that models perceptual and acoustic measures together. By modeling acoustic measures as predictors of perceived phonetic convergence, this paradigm has the potential to reconcile some of the diverse and inconsistent findings currently reported in the literature.